Survival Mechanism of The Shia Community Post-Shia–Sunni Sampang Conflict in 2012 - Muhammad Aziz Khoiri; Leila Chamankhah (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
The purpose of this article is to discuss the mechanisms that the Shia community of Rusunnawa Puspa Agro Sidoarjo adopted to survive the sectarian conflict of 2012. This research uses a qualitative approach, using a snowball sampling technique with key informants, Ustad Tajul Muluk and Ustad Iklil. Data collection techniques include in-depth interviews. The result is indicative of the fact that the Shia community took three approaches to survive the sectarian clashes. First, the Shia community attempted to reduce its daily expenses to the most urgent needs. Second, the Shia community members used an alternative subsystem of working as coconut shelling labor, farming the surrounding land, and raising goats and chickens to help meet their daily needs. Third, the Shia community members got a governmental network in the form of jadup money,[1] in the form of the patron-client relationship. This research also shows that the Shia community needs to get social support because material assistance is not enough [1] - Jadup is the acronym of jatah hidup, and Jatah is a financial help which is either provided by the government, or parents, or even one’s boss, but not because one has done something, but rather, because it is part of one’s right.